Implementation of Maqashid Syari’ah as a Guideline for Formulating Islamic Economic Transformation: Implementasi Maqashid Syari’ah sebagai Pedoman Perumusan Transformasi Ekonomi Syariah - Abdul Rahman Ramadhan (Syamilah Publishing, 2024)
This research aims to explore the understanding of the role of maqashid syari’ah in formulating public policies that support the transformation of the Islamic economy. This research will also identify the challenges faced in the implementation of maqashid syari’ah principles in the context of an evolving economy. Islamic economics has grown and developed rapidly in recent decades in response to the needs of the Muslim community for an economic system that is in accordance with Islamic principles. Maqashid syari’ah is a set of ethical principles that summarize the main objectives of Islamic law. These principles include the protection of religion, soul, offspring, mind and property. This research is qualitative research. Data collection in this research uses literature study. The data used in this research comes from secondary data in the form of books, scientific articles and official websites that have information relevant to research topics such as maqashid syari’ah and Islamic economics. The results of this study show that the integration of maqashid syari’ah in public policy has great potential to achieve economic justice, fair income distribution, and protection of individual rights. Despite facing complex obstacles such as lack of understanding and coordination, countries that implement these principles tend to have better and more inclusive economic performance. The principles of maqashid syari’ah that safeguard human religion, intellect, soul, offspring, and property can provide alternative solutions to address contemporary economic issues in order to achieve sustainable economic growth.